Evaluation of Student Achievement Levels: A Framework for Advancing Academic Outcomes - Alsaadi, Amera Eid (Arab Journal for Sciences and Research Publishing, 2025)
The current study aimed to measure the impact of educational plans based on accurate classification in improving students’ academic performance, as well as to assess the teachers’ ability to classify students objectively and precisely, The research population consisted of third-grade female elementary students, and the sample included (41) students, The study adopted the procedural approach as its methodology and employed various tools, including pre- and post-diagnostic and analytical tests, classroom observations, achievement records, performance reports, the “Madrasati” platform, and data analysis programs (Excel), The study reached several key findings, the most notable of which are:1.Student level analysis is an effective and essential tool for improving academic performance and enhancing learning outcomes in a systematic and realistic manner, The results confirmed that the accuracy of level analysis and the use of diverse assessment tools contribute to a deeper understanding of students’ needs, which positively reflects on the design of effective educational plans that take into account differences in their levels, whether in remedial or enrichment aspects.2. The study also highlighted the importance of linking analysis results with blended learning and utilizing the tools of the “Madrasati” platform to support self-directed and guided learning, along with continuous follow-up on the implementation of plans and analyzing results over two time periods to compare progress and assess the actual impact. The teacher’s role emerged as a central factor in the success of this approach, indicating the need for specialized training programs to enhance teachers’ competencies in analyzing levels and building effective teaching plans. The study made several recommendations: the most important of which is the necessity of integrating the effectiveness of student classification within the school planning system and activating the role of parents as partners in the educational process through effective and continuous communication.